2003
DOI: 10.1038/sj.onc.1206834
|View full text |Cite
|
Sign up to set email alerts
|

Ras oncogene directs expression of a differentially sialylated, functionally altered β1 integrin

Abstract: Intense investigation has centered on understanding the regulation of integrin cell adhesion receptors. In the present study, we propose that variant N-glycosylation represents an important mechanism for regulation of beta1, but not beta3 or beta5 integrins. We find that expression of oncogenic ras in HD3 colonocytes causes increased alpha2-6 sialylation of beta1 integrins, whereas expression of dominant-negative ras induces decreased alpha2-6 sialylation, relative to cells with wild-type ras. In contrast, nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
128
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 33 publications
2
128
2
Order By: Relevance
“…Many studies suggested that an increased cell surface sialic acid content in cancer cells is caused by up-regulating of sialyltransferase (20)(21)(22)(23)(24) and depended on the mrnA levels of sialyltransferase gene (25). In breast cancer, the sialyltransferase (α2,3-st), is mainly responsible for catalyzing sialic acid to form α2,3-sialic acid residues (26).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested that an increased cell surface sialic acid content in cancer cells is caused by up-regulating of sialyltransferase (20)(21)(22)(23)(24) and depended on the mrnA levels of sialyltransferase gene (25). In breast cancer, the sialyltransferase (α2,3-st), is mainly responsible for catalyzing sialic acid to form α2,3-sialic acid residues (26).…”
Section: Discussionmentioning
confidence: 99%
“…For example, GnT-V, GnT-III, ST6GalNAc I, and ST6Gal-I directly modify carbohydrate structures on ␤ 1 integrin and affect integrin activity. [33][34][35][36] These changes in N-glycosylation 33,37 or O-glycosylation 36 of ␤ 1 integrin lead to altered cell morphologic features and behavior. B4GALNT3 modifies N-and O-glycans decorated with GlcNAc in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…GnT-V, GnT-III, ST6GalNAc I, and ST6Gal-I were found to directly modify carbohydrate structures on h1-integrin and affect integrin activity (8)(9)(10)(11). These changes in Nglycosylation (8,30) or O-glycosylation (11) of h1-integrin lead to altered cell morphology and behavior. Furthermore, GnT-III was found to modify carbohydrates on epidermal growth factor receptor and inhibit ERK-mediated neurite outgrowth in PC12 cells (31).…”
Section: Discussionmentioning
confidence: 99%